Efecto de la fertilización orgánica en parámetros morfológicos y productivos del cultivo de maíz en la finca comuna el Cambio. - Gonzalez Valdiviezo, Jarnette Gissella (Machala : Universidad Técnica de Machala, 2022)
Corn is a crop of global and national importance for the contribution it makes to human and animal nutrition due to its high content of mineral, protein and vitamin content; in any of its phenological stages. The experimental type research was carried out in the Commune The Change, located on the trunk road of the coast, near The Change, province of Oro; the geographical coordinates: 03°17’52.28 South Latitude and 79°53’18.15” the West longitude, at an altitude de 12 meters above sea level. For the development of the experiment, a simple Latin square was used, where a study factor composed of four treatments, replicated four times, was manipulated, generating 16 experimental units, and where the double block technique was applied due to the presence of two uncontrolled factors. The treatments under study were 0, 15, 20, 25 t ha^-1 of fresh bovine manure, which were assigned to the experimental units completely at random in each columna and row independently; there are no replicas within the columna and row. To find out whether or not there were statistical differences between treatments, the intergroup factorial ANOVA test was performed, after fulfilling the assumptions of Independence of errors, data normality, homogeneity variance, and additivity of the block treatments. The variables measured were plant height, leaf length and width, stem diameter, number of total leaves, fruit per plant, ear length and diameter, 100-seed weight and dry grain yield. The hypothesis contrast shows that there is a statistical difference between the different amounts of fresh cattle manure applied as a function of morphological and agronomic parameters; and a favorable response of the corn crop associated with the increase of the organic amendment. At 30 (52.3 cm) , 60 (222.6 cm), 90 (233.7 cm) and 120 (234.4 cm) days after planting, T3 (25 t ha^-1 of fresh manure) achieved the highest plant height values statistically different from the rest of the treatments; as well as for the stem diameter, which reached the 30 (13.5 mm), 60 (15.9 mm), 90 (17.0 mm) and 120 (16.4 mm) days after planting, number of total leaves obtained at 30 (7.3 leaves), 60 (11.3 leaves), 90 (12.6 leaves) y 120 (11.0 leaves) days after planting; leaves length which reached the 30 (86.1 cm), 60 (104.7 cm), 90 (107.8 cm) and 120 (102.7 cm) days after planting; and width of leaves, which he obtained at 30 30 (6.6 cm), 60 (8.0 cm), 90 (8.6 cm) and 120 (7.5 cm) days after planting. At 120 days after planting, T3 (25 t ha-1 of fresh manure) reached the highest values of fruit per plant in the crop, (2.8 fruits), statistically different from the rest of the Treatment, which reached 2.2 fruits (20 t ha^-1 of fresh manure), 1.7 fruits (15 t ha^-1 of fresh manure) and 1.6 fruits (0 t ha^-1 of fresh manure). At 120 (18.0 cm) days after planting on T3 (25 t ha^-1 of fresh manure) reached values for ear length per plant at harvest, and statistically different from the rest of the treatments. At 120 (18.0 cm) days after planting on T3 (20 t ha^-1 of fresh manure) achieved the highest values for ear diameter per plant at harvest, statistically different from the rest of the treatments. In relation to the variable 100-seed weight at harvest at 120 days, when the following were applied 25 t ha^-1 of fresh manure was obtained 19.0 g, and statistically different from the rest of the treatments. Treatment with 25 t ha^-1 of fresh manure obtained the highest agricultural yield value in dry grains at harvest with 12.13 t ha^-1. The application of 20 t ha^-1 of fresh manure is an agronomic alternative for soil fertilization management that favors soil conservation and improvement, as well as an increase in agricultural yields.
El maíz es un cultivo de importancia mundial y nacional por el aporte que realiza en la alimentación humana y animal por su alto contenido de minerales, proteínas y vitaminas; en cualquiera de sus etapas fenológicas. La investigación de tipo experimental se realizó en la Comuna El Cambio, ubicada en la vía troncal de la costa, cerca del Cambio, provincia de El Oro; en las coordenadas geográficas: 03°17’52.28 de Latitud Sur y 79°53’18.15” de Longitud Oeste, a una altitud de 12 msnm. Para el desarrollo del experimento se utilizó un diseño cuadrado latino simple, donde se manipuló un factor de estudio, conformado por cuatro tratamientos, replicados cuatro veces, generando 16 unidades experimentales, y donde se aplicó la técnica de doble bloqueo debido a la presencia de dos factores no controlados. Los tratamientos objeto de estudio fueron 0, 15, 20, 25 t ha^-1 de estiércol vacuno fresco, los cuales fueron asignados a las unidades experimentales de forma completamente al azar en cada columna e hilera de forma independiente; sin réplicas dentro de la columna e hilera. Para conocer si se presentan o no diferencias estadísticas entre tratamientos se realizó la prueba ANOVA factorial intergrupos, previo cumplimiento de los supuestos de independencia de errores, normalidad de datos, homogeneidad de varianza y Aditividad tratamientos bloques. Las variables medidas fueron altura de la planta, largo y ancho de hoja, diámetro del tallo, número de hojas totales, frutos por plantas, largo y diámetro de mazorca, peso de 100 semillas y rendimiento agrícola en grano seco. El contraste de hipótesis demuestra que existe diferencia estadística entre las diferentes cantidades de estiércol vacuno fresco aplicadas en función de los parámetros morfológicos y agronómicos; y una respuesta favorable del cultivo del maíz asociada al incremento de la enmienda orgánico. A los 30 (52.3 cm), 60 (222.6 cm), 90 (233.7 cm) y 120 (234.4 cm) días después de la siembra el T3 (25 t ha^-1 de estiércol fresco) alcanzó los mayores valores de altura de planta diferentes estadísticamente al resto de tratamientos; al igual que para diámetro del tallo, que alcanzó a los 30 (13.5 mm), 60 (15.9 mm), 90 (17.0 mm) y 120 (16.4 mm) días después de la siembra, número de hojas totales que obtuvo a los 30 (7.3 hojas), 60 (11.3 hojas), 90 (12.6 hojas) y 120 (11.0 hojas) días después de la siembra; largo de la hoja que alcanzó a los 30 (86.1 cm), 60 (104.7 cm), 90 (107.8 cm) y 120 (102.7 cm) días después de la siembra; y ancho de la hoja, que obtuvo a los 30 (6.6 cm), 60 (8.0 cm), 90 (8.6 cm) y 120 (7.5 cm) días después de la siembra. A los 120 días después de la siembra, el T3 (25 t ha^-1 de estiércol fresco) alcanzó los mayores valores de fruto por planta en la cosecha (2.8 frutos), estadísticamente diferente al resto de tratamientos, que alcanzaron 2.2 frutos (20 t ha^-1 de estiércol fresco), 1.7 frutos (15 t ha^-1 de estiércol fresco) y 1.6 frutos (0 t ha^-1 de estiércol fresco). A los 120 (18.0 cm) días después de la siembra el T3 (25 t ha^-1 de estiércol fresco) alcanzó valores de largo de mazorca por planta en la cosecha, superiores y estadísticamente diferentes al resto de tratamientos. A los 120 (18.0 cm) días después de la siembra el T3 (25 t ha^-1 de estiércol fresco) alcanzó los mayores valores de diámetro de mazorca por planta a la cosecha, estadísticamente diferente al resto de tratamientos. En relación con la variable peso de 100 semillas a la cosecha, realizada a los 120 días, cuando se aplicaron 25 t ha^-1 de estiércol fresco se obtuvo 19.0 g, mayor y estadísticamente diferente al resto de tratamientos. El tratamiento con 25 t ha^-1 de estiércol fresco obtuvo el mayor valor rendimiento agrícola en grano seco a la cosecha con 12.13 t ha^-1. La aplicación de 25 t ha^-1 de estiércol vacuno fresco es una alternativa agronómica de manejo de la fertilización edáfica que favorece la conservación y mejoramiento del suelo, así como, el incremento del rendimiento agrícola.
Keywords: ESTIÉRCOL; CULTIVO; MAÍZ; PRODUCCIÓN